Energy Citizenship and Its Application in the Energy Transition in Poland - Iwińska, Katarzyna (Stan Rzeczy, 2025)
Energy citizenship, a concept that frames individuals and communities as active participants in energy transitions, has gained significant attention as a critical element in achieving sustainable and just energy systems. This paper builds on Devine-Wright’s (2007) foundational work by exploring the concept of energy citizenship as a multidimensional and evolving phenomenon. It analyses current trends in energy citizenship, including community energy initiatives, energy transition, and justice at the intersection of climate action, environmental awareness, and European research. While existing research has developed theoretical foundations, the operationalisation of energy citizenship across diverse socio-political contexts remains underexplored. Using a recently validated scale to measure perceptions of energy rights and responsibilities, this paper presents a preliminary analysis of Polish energy citizenship. The findings reveal strong public support for fundamental energy rights. However, attitudes concerning personal responsibility or willingness to act are significantly less positive. This paper provides a summary of theoretical and practical pathways towards a more equitable and inclusive sustainable energy system, while emphasising the need for targeted initiatives to address these challenges.